2015
DOI: 10.1002/term.2086
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted therapeutic benefits of factors derived from stem cells from human exfoliated deciduous teeth for acute liver failure in rats

Abstract: In acute liver failure (ALF), a poorly controlled innate immune response causes massive hepatic destruction, which elicits a systemic inflammatory response, progressive multiple organ failure and ultimate sudden death. Although the liver has inherent tissue-repairing activities, its regeneration during ALF fails, and orthotopic liver transplantation is the only curative approach. Here we show that a single intravenous administration of stem cells derived from human exfoliated deciduous teeth (SHEDs) or of SHED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…10 Stem Cells International that expressed Arginase-1, Ym-1, and CD206 in vitro. These findings were further proved in vivo [124][125][126], where intravenous administration of SHED-CM in a bleomycin-induced acute lung injury mouse model, reduced lung fibrosis, and enhanced survival rates. These therapeutic effects were elicited through reducing the expression of proinflammatory cytokines and fibrotic markers such as α-smooth muscle actin, thereby reducing fibrosis by altering proinflammatory M1 into an anti-inflammatory M2 phenotype [112,113,126].…”
Section: Shed-cm In the Therapy Of Cardiopulmonary Injuriesmentioning
confidence: 66%
“…10 Stem Cells International that expressed Arginase-1, Ym-1, and CD206 in vitro. These findings were further proved in vivo [124][125][126], where intravenous administration of SHED-CM in a bleomycin-induced acute lung injury mouse model, reduced lung fibrosis, and enhanced survival rates. These therapeutic effects were elicited through reducing the expression of proinflammatory cytokines and fibrotic markers such as α-smooth muscle actin, thereby reducing fibrosis by altering proinflammatory M1 into an anti-inflammatory M2 phenotype [112,113,126].…”
Section: Shed-cm In the Therapy Of Cardiopulmonary Injuriesmentioning
confidence: 66%
“…Further, it has been demonstrated by cytokine array analyses that SHED‐CM contain numerous factors such as OPG, TIMP‐1, TIMP‐2, ANG, MCP‐1, VEGF‐A and multiple liver‐regeneration factors, which are involved in anti‐apoptosis/hepatocyte protection, angiogenesis, macrophage differentiation and the proliferation/differentiation of liver progenitor cells. Subsequently, it was found that SHED‐CM injection into a d ‐galactosamine‐induced rat model of acute liver failure markedly improves the condition of the injured liver and animal survival rates (Matsushita et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Dental pulp stem cells secrete a broad repertoire of trophic and immunomodulatory factors that have the potential to treat various types of intractable diseases [22][23][24][25][26][36][37][38][39][40][41]. We previously showed that the factors in SHED-CM improve PNI in a rat model of sciatic nerve transection; however, the mechanisms involved in repairing the damaged nerve have been elusive.…”
Section: Discussionmentioning
confidence: 99%